Diastereomeric resolution of 3‐chloromandelic acid with threo‐(1S, 2S)‐2‐amino‐l‐p‐nitrophenyl‐1, 3‐propanediol. Issue 11 (9th September 2021) - Wang, Jie; Ao, Qiong; Peng, Yangfeng; Feng, Cai
Abstract: An optical resolution of 3‐chloromandelic acid (3‐ClMA) using threo‐(1 S, 2 S )‐2‐amino‐l ‐ p ‐nitrophenyl‐1, 3‐propanediol ([ S, S ]‐SA) as a resolving agent was presented. The effects of the type of solvents, the amount of solvent, molar ratio of the resolving agent to racemate and filtration temperature on resolution were investigated. Under the optimal resolution conditions, the content of less soluble salt reached 98%, and the resolution efficiency was as high as 94%. The weak intermolecular interactions (such as hydrogen bond, halogen bond, CH/π and van der Waals interactions) and molecular packing mode in crystal structure of the less soluble salt ( R )‐3‐ClMA( S, S )‐SA were investigated. A wall‐like 2‐D hydrogen‐bonding network and hydrophobic structure between hydrogen‐bonding walls were revealed. ( S, S )‐SA was also used to resolve 2‐ClMA and 4‐ClMA respectively and the corresponding less soluble salts ( R )‐2‐ClMA·( R, R )‐SA and ( R )‐4‐ClMA·( R, R )‐SA were obtained using threo‐(1 R, 2 R )‐2‐amino‐l ‐ p ‐nitrophenyl‐1, 3‐propanediol (( R, R )‐SA) as a resolving agent. In addition, two other resolving agents, ( R )‐ɑ‐phenethylamine (( R )‐PEA) and ( R )‐ N ‐benzyl phenethylamine (( R )‐BPA) reported in the literature for the resolution of 3‐ClMA were examined along with the newly proposed resolving agent, ( S, S )‐SA. The crystal structures of the resulting less soluble salts ( R )‐3‐ClMA·( S, S )‐SA, ( R )‐3‐ClMA·( R )‐PEA and ( R )‐3‐ClMA·( R )‐BPA were compared and examined. Abstract :